The role of maxillary canines in forensic odontology - Mohammed Nahidh; Haider M A Ahmed; Abeer B Mahmoud; Sawsan M Murad; Braa' S Mehdi (College of Dentistry/ University of Baghdad, 2013)
Background: This study aimed to determine the gender of a sample of Iraqi adults utilizing the mesio-distal width of maxillary canines, inter-canine width and standard maxillary canine index, and to determine the percentage of dimorphism as an aid in forensic odontology. Materials and methods: The sample included 200 sets of study models belong to 200 subjects (100 males and 100 females) with an age ranged between 17-23 years. The mesio-distal crown dimension was measured manually, from the contact points for the maxillary canines (both sides), in addition to the inter-canine width using digital vernier. Descriptive statistics were obtained for the measurements for both genders; independent samples t-test was performed to evaluate the gender difference, percentage of dimorphism was obtained and discriminant function statistics were used for gender identification in addition to the percentages of gender identification accuracy. Results: Generally, the mesio-distal width of the maxillary canine and the inter-canine width were larger in males than females with a high significant difference. The accuracy of genders determination using standard maxillary canine index was 44% for males, 74% for females and 59% for the combined sample, while it was 70% for males, 76% for females and 73% for the combined sample using discriminant function statistics depending upon the canines, inter-canine widths and maxillary canine index. The percentages of dimorphism were 6.13% for the canine mesio-distal width and 4.66% for the inter-canine width. Conclusions: Maxillary canines can be used in genders identification as an aid for forensic odontology.